The Level of Student Knowledge about Reproductive Health at the Faculty of Midwifery, Medistra Lubuk Pakam - Fiyola Ladyvia; Natasha Elga Haryono; Ismah Khaerunisa (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
Reproductive health is a fundamental competency that must be mastered by midwifery students because it is closely related to professional practice in maternal and child health services. This study aims to analyze determine the level of knowledge of students of the Faculty of Midwifery at the Medistra Health Institute, Lubuk Pakam, regarding reproductive health. The study design used a quantitative descriptive approach with a cross-sectional method. The study sample consisted of 100 students selected using a purposive sampling technique. Data were collected using a structured questionnaire and analyzed using SPSS software with descriptive statistical tests and Pearson correlation. The results showed that 72% of students had a good level of knowledge, 20% had a sufficient level of knowledge, and 8% had a poor level of knowledge. The correlation analysis showed a positive relationship between knowledge level and semester (r = 0.416; p < 0.05), meaning that the higher the semester, the better the level of knowledge. The conclusion of this study indicates that the level of student knowledge about reproductive health is quite good, but it is necessary to improve continuous education through contextual learning and field-based training.